2022
DOI: 10.3389/fphar.2022.1043236
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and antioxidant activity of astragalus polysaccharide in ulcerative colitis: A systematic review and meta-analysis of animal studies

Abstract: Background: Accumulated evidence indicates that astragalus polysaccharide (APS) may have a beneficial impact on ulcerative colitis (UC) by suppressing inflammation and decreasing oxidative stress. Nevertheless, the credibility of the evidence for this practice is unclear. Therefore, we intended to conduct a systematic review and meta-analysis of animal studies to assess the anti-inflammatory and antioxidant activity of APS when used in the treatment of UC.Methods: Electronic bibliographic databases including P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…Amino salicylates scavenge ROS superoxide and recover SOD activity, NF-kB, MPO, and proinflammatory cytokine production. The inhibitory effect of 5-aminosalicylic acid and acetylsalicylic acid on NETosis was proved, making them a potentially ideal supplementary therapy in NET-related kidney disorders (205,206).…”
Section: Antioxidantsmentioning
confidence: 99%
“…Amino salicylates scavenge ROS superoxide and recover SOD activity, NF-kB, MPO, and proinflammatory cytokine production. The inhibitory effect of 5-aminosalicylic acid and acetylsalicylic acid on NETosis was proved, making them a potentially ideal supplementary therapy in NET-related kidney disorders (205,206).…”
Section: Antioxidantsmentioning
confidence: 99%
“…Amino salicylates scavenge ROS superoxide and recover SOD activity, NF-kB, MPO, and proinflammatory cytokine production. The inhibitory effect of 5-aminosalicylic acid and acetylsalicylic acid on NETosis was proved, making them a potentially ideal supplementary therapy in NET-related kidney disorders (205,206).…”
Section: Antioxidantsmentioning
confidence: 99%
“…Hu et al performed a meta-analysis and concluded that APS treatment dramatically relieved colonic damage by reversing the levels of DAI, CMDI, CHS, TNF-α, IL-6, IL-1β, MPO, MDA, and SOD [104]. Pre-and post-addition of APS (100 µg/mL) could downregulate the expression of inflammation indicators and levels of short circuit current while increasing the mRNA expression of ZO-1 and occludin in LPS-infected Caco-2 cells [105] (Table 3).…”
Section: Astragalus Polysaccharidementioning
confidence: 99%